ESP32 CAM Flood Warning System with Fuzzy Logic: Sistem Peringatan Banjir ESP32 CAM dengan Logika Fuzzy - Roy Andi Subagia; Inggit Marodiyah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Flood-prone areas require reliable early warning systems to support timely monitoring and response. Specific Background: Kedungbanteng Village, Sidoarjo Regency, experiences recurring flooding due to its lowland geographical conditions and proximity to major rivers. To address this issue, a flood warning system was developed using an ESP32-CAM microcontroller, an ultrasonic sensor, a camera module, fuzzy logic processing, indicator lights, an alarm, and Telegram-based notifications. Knowledge Gap: Previous flood detection approaches have faced challenges related to measurement accuracy and rapid information delivery, highlighting the need for a system capable of real-time monitoring and communication. Aims: This study aimed to develop and test Roy’s Flood Alarm Detector (RFAD) for real-time water level detection and remote flood monitoring. Results: The developed system measured water levels using an ultrasonic sensor, classified conditions into safe, alert, and emergency categories, activated visual and audio warnings at predefined thresholds, and transmitted notifications and images through Telegram. The ESP32-CAM successfully supported remote monitoring, while fuzzy logic was utilized to process water-level data. Novelty: The study integrates ESP32-CAM technology, ultrasonic sensing, fuzzy logic, camera-based visual verification, and Telegram communication within a single flood warning platform. Implications: The proposed system provides timely flood information that can support preventive actions and monitoring activities in flood-prone communities.Highlights: Real-time water-level monitoring was achieved through ultrasonic sensing and remote communication. Automatic alerts were generated using visual indicators, buzzer signals, and mobile notifications. Camera-based verification p Keywords: ESP32-CAM; Flood Warning System; Fuzzy Logic; Ultrasonic Sensor; Telegram Notification